Outreach education for integration of HIV/AIDS care, antiretroviral treatment, and tuberculosis care in primary care clinics in South Africa: PALSA PLUS pragmatic cluster randomised trial. (21st April 2011) - Zwarenstein, Merrick; Fairall, Lara R; Lombard, Carl; Mayers, Pat; Bheekie, Angeni; English, René G; Lewin, Simon; Bachmann, Max O; Bateman, Eric
Abstract : Objective To investigate whether PALSA PLUS, an on-site educational outreach programme of non-didactic, case based, iterative clinical education of staff, led by a trainer, can increase access to and comprehensiveness of care for patients with HIV/AIDS. Design Cluster randomised trial. Setting Public primary care clinics offering HIV/AIDS care, antiretroviral treatment (ART), tuberculosis care, and ambulatory primary care in Free State province, South Africa. Participants Fifteen clinics all implementing decentralisation and task shifting were randomised. The clinics cared for 400 000 general primary care patients and 10 136 patients in an HIV/AIDS/ART programme. There were 150 nurses. Intervention On-site outreach education in eight clinics; no such education in seven (control). Main outcome measures Provision of co-trimoxazole prophylaxis among patients referred to the HIV/AIDS/ART programme, and detection of cases of tuberculosis among those in the programme. Proportion of patients in the programme enrolled through general primary care consultations. Results Patients referred to the HIV/AIDS programme through general primary care at intervention clinics were more likely than those at control clinics to receive co-trimoxazole prophylaxis (41%, (2253/5523) v 32% (1340/4210); odds ratio 1.95, 95% confidence interval 1.11 to 3.40), and tuberculosis was more likely to be diagnosed among patients with HIV/AIDS/ART (7% (417/5793) v 6% (245/4343); 1.25, 1.01 to 1.55). Enrolment in the HIV/AIDS and ART programme through HIV testing in general primary care was not significantly increased (53% v 50%; 1.19, 0.51 to 2.77). Secondary outcomes were similar, except for weight gain, which was higher in the intervention group (2.3 kg v 1.9 kg, P<0.001). Conclusion Though outreach education is an effective and feasible strategy for improving comprehensiveness of care and wellbeing of patients with HIV/AIDS, there is no evidence that it increases access to the ART programme. It is now being widely implemented in South Africa. Trial registration Current Controlled Trials ISRCTN 24820584 .